THE MARKETING CHAIN OF RICE PRODUCTS IN ACEH PROVINCE - Teuku Saiful Bahri; Ira Manyamsari; Dedi Kurniawan; Achmad Ziyan Farabi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Rice is a leading commodity in the food crops sub-sector in Indonesia. The main problems that are often faced by paddy farmers are the low level of productivity, the lack of certainty in marketing, and fluctuations in the price of rice and high marketing margins. This research was conducted purposively in Aceh Province. The research locations chosen were Aceh Besar and North Aceh districts. The method used is descriptive analysis carried out by identifying existing Marketing Chains so that they can find out the product delivery process from marketing institutions. This analysis uses quantitative analysis by calculating the marketing margin, farmer's share, and the ratio of benefits and costs. The results of the study are that there are 3 Marketing Chains for rice in the province of Aceh. Based on the facts in the field, farmers sell directly to collectors or rice mills to make rice. The price of rice that is marketed is determined by the traders themselves according to the amount of costs required in the marketing process by each marketing agency. The suggeestion that can be given is to provide access to capital for farmers so that farmers are able to buy certified seeds which can later increase the quantity and quality of production.